2022
DOI: 10.2337/dc21-1975
|View full text |Cite
|
Sign up to set email alerts
|

Model for Integration of Monogenic Diabetes Diagnosis Into Routine Care: The Personalized Diabetes Medicine Program

Abstract: OBJECTIVE To implement, disseminate, and evaluate a sustainable method for identifying, diagnosing, and promoting individualized therapy for monogenic diabetes. RESEARCH DESIGN AND METHODS Patients were recruited into the implementation study through a screening questionnaire completed in the waiting room or through the patient portal, physician recognition, or self-referral. Patients suspected of having monogenic diabetes ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Site staff helped participants navigate and complete study procedures to help mitigate retention barriers due to limited health literacy or access. Existing studies and registries were leveraged to identify subjects with atypical diabetes for referral to RADIANT including the Monogenic Diabetes Registry at the University of Chicago [13], the Personalized Diabetes Medicine Program at the University of Maryland [14], and the Ketosis-Prone Diabetes Registry at Baylor College of Medicine [15]. Multiple advertisement tools and avenues were used to enhance awareness of RADIANT in the community, among clinicians and potential participants.…”
Section: Resultsmentioning
confidence: 99%
“…Site staff helped participants navigate and complete study procedures to help mitigate retention barriers due to limited health literacy or access. Existing studies and registries were leveraged to identify subjects with atypical diabetes for referral to RADIANT including the Monogenic Diabetes Registry at the University of Chicago [13], the Personalized Diabetes Medicine Program at the University of Maryland [14], and the Ketosis-Prone Diabetes Registry at Baylor College of Medicine [15]. Multiple advertisement tools and avenues were used to enhance awareness of RADIANT in the community, among clinicians and potential participants.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, certain patients with HNF1B or WFS1 pathogenic mutations do not present with typical extrapancreatic features; instead, they only exhibit glycaemic impairment. 30,31 In the previous studies, 32,33 although ALMS1 has been included in the monogenic diabetes genes list, the characteristics of patients with variants were not further explored.…”
Section: Totalmentioning
confidence: 99%
“…One should note that the majority of MgDs are revealed in adults, with a phenotype that may suggest T2D, and these patients are usually followed by general practitioners who may not be well informed about MgD. A recent study showed that self-referral by the patients was the most efficient way to increase the diagnosis rate of MgD [112], underlying the potential for educating patients with diabetes on this topic.…”
Section: Monogenic Diabetes Often Remain Misdiagnosedmentioning
confidence: 99%